Nitrogen Cycling in the Americas: Natural and Anthropogenic Influences and Controls - Martinelli, Luiz A.; Howarth, Robert W.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
The rate of creation of reactive nitrogen (NR) on the earth has dramatically increased in the last half century mainly due to the production of N-fertilizer through the Haber-Bosch process, fossil fuel combustion, and the cultivation of plants that fix N from the atmosphere. The anthropogenic production of NR has been especially high in developed countries of the temperate zone, such as the USA and Canada, where severe eutrophication of estuaries and coastal zones, acidification of lakes and streams, loss of biodiversity, and reduced forest productivity have become common environmental problems associated with increasing nitrogen loads to ecosystems. However, important drivers responsible for the increase of the production of NR in the temperate zone are increasingly influencing the nitrogen cycle in rapidly developing regions of the world, such as the Tropics and Sub-Tropics, including most of the countries of Latin America and the Caribbean. Advances in our understanding of the nitrogen cycle and the impact of anthropogenic activities on regional to global scales depend on the expansion of scientific studies to these fast-developing regions. This book presents a series of studies from across the Americas whose aim is to highlight key natural processes that control nitrogen cycling as well as discuss the main anthropogenic influences on the nitrogen cycle in both the tropical and temperate regions of the Americas.
Sources of reactive nitrogen affecting ecosystems in Latin America and the Caribbean: current trends and future perspectives -- A review of anthropogenic sources of nitrogen and their effects on Canadian aquatic ecosystems -- More is less: agricultural impacts on the N cycle in Argentina -- Human activities changing the nitrogen cycle in Brazil -- Assessment of nitrogen flows into the Cuban landscape -- Urban influences on the nitrogen cycle in Puerto Rico -- Nitrogen and phosphorus budgets for a tropical watershed impacted by agricultural land use: Guayas, Ecuador -- The influence of climate on average nitrogen export from large watersheds in the Northeastern United States -- Coastal eutrophication assessment in the United States -- Nitrogen cycling in tropical and temperate savannas -- Nutrient-chlorophyll relationships in tropical-subtropical lakes: do temperate models fit? -- The stable carbon and nitrogen isotopic composition of vegetation in tropical forests of the Amazon Basin, Brazil.
Keywords: Ecology .; Ecosystems; Geobiology; Ecotoxicology; Ecology; Ecosystems; Biogeosciences; Ecotoxicology